(untitled) (Plant Tissue Culture and Biotechnology, 2020)
The chemical mutagens, namely sodium azide and guanidine hydrochloride (30, 40 and 50 mM) for each were applied for the in vitro culture of Gardenia jasminoides Ellis. Eight morphological traits were evaluated to calculate the result of different concentrations of mutagens compared to control. In sodium azide, all morphological traits decreased compared to control, except the number of branches and leaves and leaf length, which increases compared to control. Unlike guanidine hydrochloride, all the morphological traits are enhanced in mutants rather than control. The polymorphism percentage resulted from genetic variation varied (57.71% in the case of sodium azide and 67.59% in guanidine hydrochloride). Hence, guanidine hydrochloride is a more powerful mutagen and causes more genetic variations and instability than sodium azide, as was reflected in morphological parameters (i.e., fresh weight, shoot length, root length, number of lateral roots, number of leaves, numbers of branches, leaf length, and leaf width) and physiological traits (i.e., chlorophyll pigmentation and carotenoids). Plant Tissue Cult. & Biotech. 30(2): 209-218, 2020 (December)